The Impact of Digital Tools on Writing Skills Development (Journal of Universal Science Research, 2024)
Digital technologies offer a multitude of options for writing practice, feedback, and creative expression, which may significantly improve writing abilities. This article examines how digital technologies have a significant impact on writing teaching, practical methods for incorporating these resources into classroom environments, and ideas for optimizing their positive educational effects. Teachers can develop skilled writers who can adjust to the changing needs of digital communication by utilizing digital technologies.